IN VITRO CYTOTOXIC AND APOPTOTIC EFFECT OF PASSIFLORA FOETIDA AGAINST CERVICAL CANCER CELLS AND ITS FOURIER TRANSFORM INFRARED PROFILING - Shankar P, Dheeban; S, Basker; S, Karthik (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: This study was aimed on the analysis of cytotoxic and apoptotic action of Passiflora foetida followed by identification of the functional groups responsible for the activity. Methods: In this study, cytotoxic and apoptotic effect of methanol extract of P. foetida were analyzed by treating HeLa cell line cultures with different concentrations of the extract (25, 50, 75, 100, and 125 Î¼g/ml), and thereby the activity was ratified by 3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide (MTT) assay and propidium iodide staining. The functional groups of the bioactive compounds for the effectiveness of the treatment were known by Fourier transform infrared spectroscopy analysis (FTIR). Results: The cytotoxic activity was found to be increased in a dose-dependent manner with inhibitory concentration value of 21.55 Î¼g/ml and showed an effective apoptosis. Further, FTIR analysis confirmed the presence of functional groups of alkaloids, flavonoids, saponins, steroids, terpenoids, phenols and cardiac glycosides which might be responsible for the aforesaid activity. Conclusion: The cytotoxic and apoptotic action of P. foetida was proved to be very effective, and the tenable functional groups were identified.